Blood pressure control and left ventricular echocardiographic progression in hypertensive patients: an 18-month follow-up study - Yang, Yan; Li, Yan; Zhu, Limin; Xu, Jianzhong; Tang, Xiaofeng; Gao, Pingjin (Frontiers in Cardiovascular Medicine, 2023)
Objectives The impact of blood pressure (BP) control and its timing on left ventricular (LV) structure and function remains unclear. The present study was to evaluate whether BP control correlated with conventional LV geometry and function indexes or global longitudinal strain (GLS) progression, and when echocardiographic changes would occur in essential hypertension. Methods and results A total of 62 participants (mean age 55.2 ± 11.5, male 71.0%) with uncontrolled hypertension were enrolled in the longitudinal study. Patients were followed up at the 6-month and 18-month, when echocardiographic measurements were performed and BP control was evaluated during the follow up period. At the 6- and 18-month examination, we divided the hypertensive patients into two groups as BP controlled and uncontrolled group. Patients with BP uncontrolled (n = 33) had higher LV mass index (P = 0.02), higher left atrial volume index (P = 0.01), worse GLS (P = 0.005) and GLS changes (P = 0.003) compared with controlled BP (n = 29) at the 6-month follow-up examination. Patients with uncontrolled BP (n = 25) had higher LV mass index (P = 0.001), higher LV mass index changes (P = 0.01), higher relative wall thickness (P = 0.01), higher E/e′ (P = 0.046), worse GLS (P = 0.02) and GLS changes (P = 0.02) compared to BP controlled group (n = 24) at the 18-month follow-up examination. GLS changes were associated with BP control (β = 0.370, P = 0.004 at the 6-month examination and β = 0.324, P = 0.02 at the 18-month examination, respectively) in stepwise multivariate regression analysis. LV mass index changes was corelated with systolic BP (β = 0.426, P = 0.003) at the 18-month follow-up examination in stepwise multivariate regression analysis. Neither was GLS changes nor LV mass index changes were related to antihypertensive medication class, including combination therapy in 6- or 18-month follow up examination. Conclusions Our findings offer new clinical evidence on the association of BP control with echocardiographic changes in hypertensive patients, and, in particular, support the view that GLS progression was earlier and subtler than conventional LV geometry and function parameters. GLS changes were significant between BP controlled and uncontrolled patients even in 6-month follow-up period.